Certification of enterprises from the Republic of Moldova in the ISO 22000 and ISO 22005 system: Benefits and barriers - Boris Gaina; Svetlana Fedorchukova; Galina Kobirman (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
In order to aspire to join the EU that the Republic of Moldova (currently a candidate country) has, the main economic conditions it must satisfy are the existence of a functional market economy, as well as the ability to face competitive pressure and market forces in within the European Union. Another condition is the existence of the capacity to assume the obligations of a member state of the European Union, including adherence to the objectives of the political, economic and monetary union. One of the objectives of EU food safety policy is to protect consumers while ensuring the smooth functioning of the single market. EU legislation covers the entire food chain - "from farm to consumer" - in an integrated way and applying a "one health" approach. This desired, at the first stage, can be ensured by implementing the food safety management system - ISO 22000 and ISO 22005 which specify the basic requirements for the design and implementation of a traceability system for food and agro-food products. The given study was focused on the knowledge of the food and agro-food enterprises from the Republic of Moldova certified in this system, as well as what are the benefits but also the impediments encountered by them both during the certification period and during the activity.
Keywords: A10; C83; 330; certification in the system; food safety; benefits of certification